Analisis Faktor Yang Mempengaruhi Struktur Modal Bank Umum Syariah Di Indonesia - Putri, Seftiyana; Putrianingsih, Reni; Agnes, Rio (RIGGS: Journal of Artificial Intelligence and Digital Business, 2025)
The objective of this study is to examine the factors influencing the capital structure of Islamic Commercial Banks in Indonesia. This research uses a sample of five Islamic Commercial Banks (BUS) that published quarterly financial reports during the 2019–2023 period. The data used in this study are secondary, obtained from the official websites of Islamic banks and the Financial Services Authority (OJK). The sampling technique employed was purposive sampling, while data analysis was conducted using panel data regression tests with EViews software. The independent variables in this study include firm size (measured by total assets), profitability (ROA), and liquidity (FDR), while the dependent variable is capital structure (DER). The findings reveal that firm size and liquidity have a significant negative influence on capital structure, whereas profitability shows an insignificant negative effect.